Dissecting the importance and origin of circulating myokines in gastric cancer cachexia - Sierzega, Marek; Drabik, Anna; Sanak, Marek; Chrzan, Robert; Richter, Piotr (Frontiers in Endocrinology, 2024)
Background Some experimental data suggest that myokines may play an important role in developing cancer-associated cachexia (CAC), but their relevance in humans remains poorly explored. In our study, we tested the hypothesis that circulating myokines are associated with the pathogenesis of CAC in a model population of gastric cancer. Methods A group of 171 treatment naïve patients with adenocarcinoma of the stomach were prospectively examined. Cachexia was defined as weight loss >5% or weight loss >2% with either BMI <20 kg/m2 or sarcopenia. A panel of 19 myokines was measured in portal and peripheral blood as well as tumour tissue and surrounding gastric mucosa. Moreover, a serum proteomic signature of cachexia was identified by a label-free quantitative proteomics with a nano LC-MS/MS system and stored in a ProteomeXchange database (PXD049334). Results One hundred (58%) patients were diagnosed with CAC. The concentrations of fatty acid-binding protein 3 (FABP3), follistatin-like 1 protein (FSTL−1), interleukin 6 (IL 6), and interleukin 8 (IL 8) were significantly higher in the peripheral blood of cachectic subjects, while leptin levels were lower. Of all the evaluated myokines, tumour tissues showed higher expression levels only for IL-15 and myostatin. However, the analysis of paired samples failed to demonstrate a decreasing concentration gradient between the portal and peripheral blood for any of the myokines, evidencing against their release by the primary tumour. Proteomic analysis identified 28 proteins upregulated and 24 downregulated in the peripheral blood of patients with cachexia. Differentially expressed proteins and 5 myokines with increased serum levels generated a significant protein-protein interaction network. Conclusions Our study provides clinical evidence that some myokines are involved in the pathogenesis of cachexia and are well integrated into the regulatory network of circulating blood proteins identified among cachectic patients with gastric cancer.